Şemail-i şerif, [early 18th century?]. - Ayn-ı Ekber Mehmet Efendi; Şehri Emin Efendizade Mehmet Reşat (1700)
Elegant copy of Ayn-ı Ekber Mehmet Efendi's (d.1722) versified Turkish work on the characteristics of the Prophet.
Shelfmark: Ann Arbor, University of Michigan, Special Collections Research Center, Isl. Ms. 411
Origin: Lacks dated colophon ; statement on 'title page' identifying work and author appears to be dated 1160 [1747] and provides a rough terminus ante quem ; paper, decoration, etc. also certainly suggest 18th century.
Former shelfmark: "478 T. De M. [i.e. Tammaro De Marinis]" inscribed in pencil on verso of front flyleaf.
Binding: Pasteboards covered in maroon leather ; Type II binding (with flap), likely two-piece binding (seam of overlapping flanges visible at spine) ; pastedowns and flyleaves in pink surface-dyed, textured wove paper (embossed in vegetal pattern of large leaves, flowers and vines) ; upper and lower covers carry tooled and gold-painted border and outline of central panel ; sewn in golden yellow thread, two stations ; worked chevron endbands in magenta and dark blue, good condition ; overall in good condition with minor abrasion, etc.
Support: European laid paper with 11 laid lines per cm. (vertical), chain lines spaced 22-24 mm. apart (horizontal), and watermark of grapes (raisin) under crown (see p.18, 28, etc.), transluscent and crisp though sturdy, well-burnished to glossy.
Keywords: Manuscripts, Turkish / Michigan / Ann Arbor.; Hadith / Criticism, interpretation, etc. / Early works to 1800 / http://id.loc.gov/authorities/subjects/sh2008105464; Headpieces (layout features) / 18th century. / aat